THE RELATIONSHIP BETWEEN WORK LIFE BALANCE AND HYBRID WORK ON EMPLOYEE PERFORMANCE AT PT INDOBEST ARTHA KREASI - Amilianti, Dea (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The study aims to determine the relationship between Work Life Balance and Hybrid Work on Employee Performance partially or simultaneously. The research method the author uses is quantitative method and the data used is primary data. This research sample amounted to 70 employees at PT Indobest Artha Kreasi as respondents. The sampling method taken using nonprobability sampling using saturated sampling technique, using a questionnaire instrument to collect data. The results showed that: 1).There is a relationship between Work Life Balance on employee performance partially with a moderate level of interpretation 2). There is a relationship between Hybrid Work on Employee Performance partially with a moderate level of interpretation. 3). There is a relationship between Work Life Balance and Hybrid Work on Employee Performance simultaneously with a moderate level of interpretation.The research implication shows that there is a relationship between Work Life Balance and Hybrid Work on Employee Performance.